Anti-Inflammatory Properties of Acetone Extract of Green Coffee Beans: An In Vitro Assay - Chukwuemeka, Chimezie Alexdaniel; Ofoegbu, Chukwudi Jude; Amadi, Nnaemeka Promise (Sciences of Phytochemistry, 2026)
This study evaluated the anti-inflammatory potential of the acetone extract of green coffee beans (Coffea excelsa) using in vitro assays. The extract was assessed for its ability to inhibit protein denaturation and stabilize biological membranes using heat-induced hemolysis of human erythrocytes as a model. The extract exhibited an overall increase in inhibitory effect across the tested concentrations in both assays. In the protein denaturation assay, percentage inhibition increased from 13.10% at 100 µg/mL to 70.45% at 1000 µg/mL, with an IC₅₀ value of 249.8 µg/mL. Similarly, in the membrane stabilization assay, inhibition ranged from 21.16% to 62.06% across the same concentration range, with an IC₅₀ value of 391.6 µg/mL. Statistical analysis using one-way ANOVA followed by Dunnett’s post hoc test indicated that all tested concentrations produced significant effects compared to the control (p < 0.0001). IC₅₀ values were determined using nonlinear regression analysis (n = 3). Although the extract showed lower activity compared with acetylsalicylic acid, it demonstrated moderate anti-inflammatory activity. These effects may be associated with the presence of bioactive compounds such as phenolics and flavonoids; however, this cannot be confirmed since no phytochemical analysis was conducted in this study. Overall, these results indicate that the acetone extract of green coffee beans possesses measurable anti-inflammatory properties in vitro, suggesting that it may serve as a potential source of bioactive compounds for further investigation. Further studies, including phytochemical characterization and in vivo evaluations, are required to validate these findings.